2020
DOI: 10.1111/1475-6773.13550
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating inpatient adverse outcomes under California's Delivery System Reform Incentive Payment Program

Abstract: Objective The California Delivery System Reform Incentive Payment Program (DSRIP) provided incentive payments to Designated Public Hospitals (DPHs) to improve quality of care. We assessed the program's impact on reductions in sepsis mortality, central line–associated bloodstream infections (CLABSIs), venous thromboembolisms (VTEs), and hospital‐acquired pressure ulcers (HAPUs). Data Sources We used 2009‐2014 discharge data from California hospitals. Study Design We used a pre‐post study design with a compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…48 It has been suggested that at the national level, the main goal should be on supporting the implementation of effective IPC interventions, through appropriate regulations and funding allocation. 49 Yet, the evidence on the effectiveness of regulations remains inconclusive, with only four 25,27,44,45 out of nine 19,[22][23][24][25]27,37,44,45 interventions demonstrating a significant effect on HAI rates from mandatory reporting, national bench marking, non-payment for HAI and investment in HAI prevention. However, all were high risk of bias, apart from McKinley et al, 27 whose risk of bias was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…48 It has been suggested that at the national level, the main goal should be on supporting the implementation of effective IPC interventions, through appropriate regulations and funding allocation. 49 Yet, the evidence on the effectiveness of regulations remains inconclusive, with only four 25,27,44,45 out of nine 19,[22][23][24][25]27,37,44,45 interventions demonstrating a significant effect on HAI rates from mandatory reporting, national bench marking, non-payment for HAI and investment in HAI prevention. However, all were high risk of bias, apart from McKinley et al, 27 whose risk of bias was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Most were conducted in USA (n=25). [12][13][14]17,19,20,[22][23][24][25][26][27][29][30][31][34][35][36][37]39,40,42,[44][45][46] The remaining studies derived from England (n=2), 11,33 Taiwan (n=2), 16,21 Australia (n=1), 28 Brazil (n=1), 15 Germany (n=1), 18 Israel (n=1), 38 Italy (n=1), 43 New Zealand (n=1), 32 and Republic of Ireland (n=1). 41 Study designs included 21 ITS, 12,14,[17][18][19][20][21]24,[29][30][31][32][33][34]…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations